High conducting poly(vinyl alcohol)–ionic liquid based electrolytes for electric double layer capacitors (EDLCS) application / Liew Chiam Wen - Liew, Chiam Wen (2015)

(untitled)
PVA/ammonium acetate (CH3COONH4)–based polymer electrolytes had been prepared using solution casting technique. The effect of addition of ionic liquid onto polymer electrolytes is investigated throughout this project. Three different types of ionic liquids are added into the PVA/ammonium acetate (CH3COONH4)–based polymer electrolytes that are 1–butyl–3–methylimidazolium chloride (BmImCl), 1–butyl–3– methylimidazolium bromide (BmImBr) and 1–butyl–3–methylimidazolium iodide (BmImI). The ionic conductivity of polymer electrolyte is increased about two orders of magnitude from (1.94±0.01)×10-5 S cm-1 to (8.97±0.01) mS cm-1, (9.29±0.01) mS cm-1 and (9.63±0.01) mS cm-1 upon addition of 50 wt.% of BmImCl, 60 wt.% of BmImBr and 70 wt.% of BmImI, respectively at ambient temperature. All the polymer electrolytes follow Vogel–Tamman–Fulcher (VTF) relationship which is associated with free volume theory. The complexation between PVA, CH3COONH4 and ionic liquids is proven in Fourier Transform Infrared (FTIR) studies. Addition of ionic liquids reduces the glass transition temperature (Tg) of polymer electrolytes as proven in differential scanning calorimetry (DSC), improves the thermal stability of polymer electrolytes as shown in thermogravimetric analysis (TGA) and widens the electrochemical potential window of polymer electrolytes as shown in linear sweep voltammetry (LSV). The crystallinity of polymer electrolytes and the coherence length of crystallites are determined in X–ray diffraction (XRD) studies. Electric double layer capacitors (EDLCs) are assembled using carbon–based electrodes. The specific capacitance of EDLC containing ionic liquid– added polymer electrolytes is much higher than the EDLC containing ionic liquid–free polymer electrolyte. The electrochemical properties of the EDLCs are analyzed using cyclic voltammetry (CV), low frequency electrochemical impedance spectroscopy (EIS) and galvanostatic charge–discharge (GCD) studies.